Triacanthoneus akumalensis, a new species of alpheid shrimp (Crustacea: Caridea: Alpheidae) from an anchialine cave in Quintana Roo, Mexico - Alvarez, Fernando; Iliffe, Thomas M.; Gonzalez, Brett; Villalobos, José Luis (Zootaxa, 2012)
A new species of Triacanthoneus Anker, 2010 is described from an anchialine cave near Akumal, Quintana Roo, Mexico.Triacanthoneus akumalensis sp. nov., is the fourth species in the genus and can be distinguished from the previously de-scribed species by the position of the sharp lateral teeth on the carapace, the length and shape of the rostrum, the eyes beingcompletely concealed by the carapace, the dentition of the major chela fingers, and the shape of the telson. The presenceof a pleural process in the new species represents a new character for the genus. The description of T. akumalensis sp. nov. increases the number of caridean genera having representatives in the anchialine systems of the Yucatan Peninsula to 11.